Myra MacDonald, Defeat is an Orphan : How Pakistan Lost the Great South Asian War - Ms. Maryam Zubair (CISS Insight Journal, 2017)
The underlying premise of Defeat is an Orphan: How Pakistan Lost the Great South Asian War is how Pakistan, though a nuclear armed state since 1998, lost every time it tried to compete with India and push through its interests. A journalist who covered South Asian affairs for about three decades, the author shines light on the rivalry between India and Pakistan. She explains in detail the events starting from the 1998 nuclear tests; the Kargil war, military standoffs in 2001-2002 and 2008, the dynamics of the countries’ involvement in Afghanistan, the problem of Kashmir, militant attacks on Indian soil, failed prospects of peace and the internal dynamics that governed the relationship between the two neighbours. Although this is a book of history, the author has been unsuccessful in remaining neutral and providing an impartial account of the events she has undertaken to describe. The author’s speculation is obvious in many instances. An important such case is the presenting of the Kashmir issue as illogical and irrelevant to relations between the two neighbours. Ms. Macdonald makes the same mistake that many foreign watchers of South Asia make, that Kashmir is an irrational and unreasonable objective, and not a prime interest of the Pakistani state.